Capacity configuration of distributed photovoltaic and battery system for office buildings considering uncertainties. (1st August 2022) - Zou, Bin; Peng, Jinqing; Yin, Rongxin; Li, Houpei; Li, Sihui; Yan, Jinyue; Yang, Hongxing
Highlights: Uncertainty-based multi-objective optimal design method of PVB system was proposed. Three groups of influencing factors with uncertainty were identified and modeled. Representative values of technical indicators ( SCR and SSR ) were defined. Generic configuration indices of PV and battery capacities were proposed. The proposed indices can be used directly as guide for PVB system design. Abstract: In practice, the actual operation conditions are generally different from those assumed in the design stage, which causes uncertainties of actual building load and photovoltaic (PV) power generation. This study conducted an optimization design for PV-battery (PVB) system with consideration of these uncertainties. Three groups of factors with uncertainty, relating to outdoor conditions, building construction and indoor conditions, were discussed. An uncertainty-based multi-objective optimization design method was proposed for the PVB system based on the random simulations and weight sum method. Compared with conventional deterministic optimization method, the uncertainty-based optimization method is more likely to achieve the optimal configuration of PV and batteries in actual conditions. When the weight factors are the same, the impacts of self-consumption rate ( SCR ) on the PVB system configuration are larger than that of the self-sufficiency rate ( SSR ). The performance of the PVB system is much more sensitive to PV capacity than to battery capacity. In practice, on the premise of achieving the required SCR, the PV capacity should be maximized while the battery capacity be minimized. Representative values of technical indicators ( SCR and SSR ), of which a relative deviation of 5% covers more than 84% of all the results, were determined. Based on the representative values, the configuration indices of PV and battery capacities for office buildings in the hot-summer and cold-winter, and the IV solar resource zone of China, were proposed, and summarized in the form of table. The proposed configuration indices can be used directly as guide for PVB system design.